- Mechanism of LDH and IL-8 Involved in pancreatic cancer Pain and the Correlation of Pain Degree: LDH and IL-8 in pancreatic cancer - Xu, Xiaoqing (Journal of Medical Biochemistry, 2024)
Objective: To observe the mechanism of lactate dehydrogenase (LDH) and interleukin 8 (IL-8) in pancreatic cancer pain and their correlation with pain degree. Methods: 126 patients with pancreatic cancer who visited our hospital from January 2021 to February 2023 were selected. The patients were divided into 58 patients with low pain (1~3 points) and 68 patients with high pain (4~10 points) by visual analog scale (VAS). And 50 health examinees in the same period were selected as the healthy control group. The serum LDH and IL-8 concentrations are analyzed by enzyme-linked immunosorbent assay, as well as the subjective pain grading method scoreis analyzed. The differences in LDH and IL-8 concentrations among the three groups of patients were compared. Pearson correlation analysis was used to investigate the correlation between LDH, IL-8 concentrations and patient pain. Binary logistic regression was used to determine independent risk factors for high pain, and ROC curves were used to analyze the diagnostic efficacy of each indicator. Result: The serum LDH and IL-8 concentrations in the high pain group were exceed the low pain group’s (P5.75. Conclusion: LDH and IL-8 participate in the pain aggravation process of pancreatic cancer, and are closely related to the pain grading. The combination of LDH and IL-8 can be used as a biological indicator to evaluate the pain severity of pancreatic cancer, and provide reference for clinical diagnosis and treatment.
Keywords: Lactate dehydrogenase; Interleukin 8; Pain; Pancreatic cancer; mechanism